Dakwah Kultural di Provinsi Lampung (Filosofi Dakwah pada Makna Lambang Siger) - Deslima, Yosieana Duli (Dakwah, 2021)
Each region in Indonesia has its characteristics in the spread of da'wah, so that Islam thrives in society. The history of da'wah in Indonesia is strongly related to the Wali Songo who spread Islamic da'wah throughout Indonesia. In the 15th century, Islam entered Lampung through the culture. One cultural expression is a symbol. Symbols are representations of subjects that have a specific purpose. Symbols have two meanings, first is religious thought and practice.. Second, is a system of logical and scientific thinking, symbols are used in the sense of abstract signs.In Lampung, the Siger functions as the crown of the bride, which is iconic. Siger that is golden reflects the glory of the people of Lampung, Siger has the meaning of feminism. That according to Lampung people, women play an important role in life.Philosophy and da'wah are interconnected. The task of philosophy is to find clarity in it. In a symbol contained deep meaning. Siger Lampung has Islamic values contained, which functions to foster religious harmony in Lampung, because these religious values have been converted to the cultural values of the local community. The emblem of the Lampung people embodied in the form of Siger shows that dakwah to the people of Lampung was carried out with a cultural approach as known as cultural dakwah as practiced by the Wali Songo. Keywords:Siger, Da'wah Philosophy, Da'wah Media, Lampung.